A novel DAD type and folic acid conjugated fluorescent monomer as a targeting probe for imaging of folate receptor overexpressed cells. (28th May 2014) - Ekiz Kanik, Fulya; Ag, Didem; Seleci, Muharrem; Barlas, Firat Baris; Kesik, Melis; Hizalan, Gonul; Akpinar, Hava; Timur, Suna; Toppare, Levent
<x xml:space="preserve">Abstract</x> We describe a modification and post‐functionalization technique for a donor–acceptor–donor type monomer; 6‐(4, 7‐bis(2, 3‐dihydrothieno[3, 4‐b][1, 4]dioxin‐5‐yl)‐2H‐benzo[d][1, 2, 3]triazol‐2‐yl)hexan‐1‐amine. Folic acid was attached to the fluorescent structure. The conjugation was confirmed via NMR and Fourier transform infrared analyses. Cytotoxicity was investigated and the comparison of association of targeted monomeric structures in tumor cells was monitored via fluorescence microscopy. © 2014 American Institute of Chemical Engineers Biotechnol. Prog., 30:952–959, 2014